Effects of prenatal testosterone exposure on the development of autism‐like behaviours in offspring of Wistar rats. Issue 2 (17th January 2023) - Erdogan, Mumin Alper; Bozkurt, Mehmet Fatih; Erbas, Oytun
Abstract: Background: A neurodevelopmental disease, autism spectrum disorder (ASD) occurs in males three times more commonly than girls. Higher prenatal testosterone exposure may result in autistic‐like behaviour in boys, according to earlier research. It is unclear how fetal testosterone affects the development of autism. In this study, we tested the hypothesis that prenatal testosterone exposure in an animal model may result in autistic behaviours by modifying serotonin, dopamine, IGF‐1 and oxytocin levels. Materials and Methods: Group 1 (control, n = 6) and Group 2 (testosterone undecanoate, n = 6) of female rats were randomly assigned. For 2–3 days during the oestrus cycle, female rats were housed with a reproductive male (three females/one male). On the 10th day of gestation, rats in Group 1 received 1 ml/kg% 0.9 NaCl saline, whereas rats in Group 2 received 250 mg/kg testosterone undecanoate. Until weaning on postnatal day 21 (P21), the mothers were permitted to care for their pups. On P21, 40 littermates—10 male and female for control and 10 male and female from mothers that exposed to testosterone—were arbitrarily split up and housed. On P50, these mature rats were tested for their behaviour. The rats were then sacrificed. The brain tissue was subjected to histological examinations as well as biochemical tests for homovanillic acid (HVA), 5‐Hydroxyindoleacetic acid (5‐HIAA), oxytocin and insulin‐like growth factor‐1 (IGF‐1). Results: The groups differed significantly in the behavioural examinations (three‐chamber social test, passive avoidance learning analysis, open field test), with the testosterone‐exposed groups exhibiting autistic symptoms to a higher extent. When compared with the control groups, testosterone exposure caused significant histological changes in the hippocampus CA1 and CA3 areas, including gliosis and cell death of neurons. In the testosterone‐exposed groups, HVA, 5‐HIAA and IGF‐1 tissue expressions in the brain elevated, whereas oxytocin levels reduced. These findings point to a potential connection between neurodevelopmental disorders like ASD and exposure to testosterone during gestation. Conclusion: Overall, we revealed that prenatal testosterone exposure led to autistic traits by elevating serotonin, dopamine and IGF‐1 levels while lowering oxytocin levels. Abstract : In this work, we explored the idea that prenatal testosterone exposure may cause autistic symptoms by changing serotonin, dopamine, IGF‐1, and oxytocin levels. The testosterone‐exposed groups showed more autistic symptoms in behavioral tests. Compared to control groups, testosterone exposure produced gliosis and cell death in the hippocampus CA1 and CA3 sections. HVA, 5‐HIAA, and IGF‐1 tissue expressions increased in testosterone‐exposed groups, but oxytocin levels decreased. These data suggest a link between ASD and prenatal testosterone exposure.